Less Reproduction, More Production: Birth Control in the Early People's Republic of China, 1949–1958. Issue 3 (1st September 2019) - Mellors, Sarah
Abstract: In the early People's Republic of China (PRC), Communist officials initially placed strict constraints on birth control use, encouraging high fertility rates. However, in an effort to enhance agricultural and industrial productivity, such restrictions were gradually repealed and by the 1970s, aggressive promotion of family planning had become the norm. Drawing on both archival and oral history, this article considers the lived experience of birth control use from the founding of the People's Republic until 1958, a period that is often overlooked in studies of reproduction and contraception in modern China, but that had important implications for later trends. Despite claims that discussion of sexuality was suppressed in the PRC and an early ban on certain publications related to sexual hygiene, a considerable amount of literature on sex and birth control was published in major cities in the 1950s. Narratives on sex and birth control in women's magazines and sex handbooks, however, varied widely and access to birth control and surgeries, such as abortions and sterilizations, differed dramatically according to location, class, and education level. This essay probes the circumstances under which women or couples practiced birth control while demonstrating the diversity of contraceptive discourses and practices in the early People's Republic. Though underexplored, the early years of the PRC remain critical to histories of reproduction in China because many of the gender dynamics, socioeconomic pressures, and cultural preferences that informed contraceptive practices in the 1950s continued to do so for decades to come.